2019
DOI: 10.2174/2405520411666181102162637
|View full text |Cite
|
Sign up to set email alerts
|

Green Procedure for One-Pot Synthesis of Azelaic Acid Derivatives Using Metal Catalysis

Abstract: Background & Objective: A green one-pot synthesis of oleic acid (1) derivatives is promoted by Rare Earth Metal (REM) triflates and commercial Molybdenum dioxo dichloride (MoCl 2 O 2) in the presence hydrogen peroxide as a green oxidant. Results: The protocol permits to govern the oxidation selectivity by simply choosing the proper combination of Mo and Sc catalysts. Conclusion: Methyl oleate epoxide 2a and azelaic acid 6 thus obtained are valuable industrial intermediates for synthesizing bio-compostable plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…al. [ 36 ]. Rare earth metal (REM) triflates and commercial molybdenum dioxo dichloride (MoCl 2 O 2 ) in the presence hydrogen peroxide allowed a selective oxidation of methyl oleate to azelaic acid or to methyl oleate epoxide.…”
Section: Azelaic Acid Synthetic Routesmentioning
confidence: 99%
“…al. [ 36 ]. Rare earth metal (REM) triflates and commercial molybdenum dioxo dichloride (MoCl 2 O 2 ) in the presence hydrogen peroxide allowed a selective oxidation of methyl oleate to azelaic acid or to methyl oleate epoxide.…”
Section: Azelaic Acid Synthetic Routesmentioning
confidence: 99%
“…To overcome these drawbacks and maintain the good catalytic performances of metal oxides, we envisioned to exploit rare earth elements. Amongst the most available of these compounds, the clean and cheap lanthanum oxide [4,17] has found a wide range of applications [18][19][20], comprising that to function as a catalyst for glycerol polymerization. Previous papers showed that a lanthanum-impregnated catalyst is the most active but the least selective, with glycerol dehydration to acrolein as the main side reaction [21].…”
Section: I) Direct Etherification Of Glyerol Under Basic Conditionsmentioning
confidence: 99%